Synthesis of porous geopolymer sphere for Ni(II) removal. Issue 20 (15th October 2021) - Tan, Tee How; Mo, Kim Hung; Lai, Sai Hin; Ling, Tung-Chai
Abstract: Maintaining a high quality of water resources is always the top priority as water is highly essential in many aspects. However, contamination of water resources, especially due to the improper discharge of industrial wastewater is drawing attention. Poorly or untreated industrial wastewater is usually severely polluted with hazardous materials such as heavy metals. Therefore, this study intended to prepare a facile-fabricated porous geopolymer sphere and investigate its potential as an adsorbent for the removal of Ni(II) from wastewater. Porous geopolymer spheres can be beneficial for direct use in packed bed systems and can be retrieved easily upon being exhausted. Results demonstrated that at the equilibrium contact time of 48 h, the Ni(II) uptake capacity of porous geopolymer spheres was approximately 3.4 times greater than non-foamed geopolymer spheres. The large pore size and open porosity network that exist in porous geopolymer spheres enhance the adsorption performance as these factors allow easy penetration of Ni(II). The optimum pH was found to be pH 5. The pH can greatly affect the removal performance, where low pH results in competition for binding sites between H + and Ni(II), while high pH induces the precipitation of Ni(OH)2 . The maximum Ni(II) removal capacity obtained from the isotherm study was 19.94 mg/g.